Application Value of Gastroenterography Combined With CT in the Evaluation of Short-Term Efficacy and Prognosis in Patients With Esophageal Cancer Radiotherapy - Xue, Liangliang; E, Linning; Wu, Zhifeng; Guo, Dongqiang (Frontiers in Surgery, 2022)
Purpose:To observe the application value of gastroenterography combined with CT in the evaluation of short-term efficacy and prognosis in patients with esophageal cancer radiotherapy. Methods:The clinical data of 207 patients with esophageal cancer treated by radiotherapy in our hospital from January 2015 to December 2020 were collected retrospectively. All patients received gastroenterography and CT examination before and after radiotherapy, and the patients were followed up for 1 year, and the evaluation value of their short-term efficacy and prognosis was observed. Results:After radiotherapy, the length diameter, short diameter and volume of lymph node were lower than those before radiotherapy. The length diameter, short diameter and volume of lymph node in good efficacy group and good prognosis group were lower, and the objective response rate in good prognosis group was higher. The AUC of the length diameter, short diameter and volume of lymph node to evaluate the short-term efficacy of patients with esophageal cancer were 0.738, 0.705 and 0.748 respectively, and the AUC to evaluate the prognosis of patients with esophageal cancer were 0.751, 0.776 and 0.791 respectively. Conclusion:Gastroenterography combined with CT has a good application value in the evaluation of short-term efficacy and prognosis in patients with esophageal cancer radiotherapy.